Analysis of a boxing match - A pilot study - Siska, L.; Brodani, J. (Journal of Physical Education and Sport, 2016)
The focus of this article is in creating a timeline of a boxing match. We observed 3 semi-final matches of later winners in weight categories of 64kg, 69kg and 75kg. We divided the observed parameters into inactive phases, active phases (punch activities) and clinches. Consequently we further divided the active phases to three more parameters which are: the actual attack, the actual attack with contra attack of the opponent and the clash. We observed the frequency and time duration of individual phases. In the second part of the experiment we tried to divide the match into 5 seconds intervals where we observed the number of initiated active phases and we determined average time, frequency and time duration of inactive phases longer than 4 seconds. The average active phase is 1.2 +/- 0.8 seconds and inactive phase's duration was 2.3 +/- 1.8 seconds. The actual attack lasts 0.7 +/- 0.2 seconds where around 1/4 of the attacks consist of multiple punches. The actual attack with the opponent's contra attack lasts 0.9 +/- 0.2 seconds and the clash between 1.9 +/- 0.9 seconds. The ratio of the actual attacks and clashes is approximately the same. The average number of active phases for an individual round is 47.3 +/- 3.8 seconds and the number of initiated active phases for each 5 seconds is 1.3 +/- 0.8. The average duration of an inactive phase longer than 4 seconds is 5.6 +/- 1.7 seconds; the average frequency of inactive phases longer than 4 seconds of an individual round is 7.6 +/- 1.9 repeats. The time between the two consecutive inactive phases longer than 4 seconds is 22.6 +/- 11.2 seconds. The results of this experiment can be directly applied into the training process with an immediate effect. This is especially applicable to the conditional training. This was one of the main impulses for conducting this research. All the results are also applicable for diagnostic reasons.